2017
DOI: 10.4103/0300-1652.218417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcomes of tuberculosis management in private for profit and private-not-for profit directly observed treatment short course facilities in Lagos State, Nigeria

Abstract: Background:The engagement of private practitioners in the public-private mix of tuberculosis (TB) management started in 2007 in Lagos State Nigeria. This study compared the treatment outcomes of patients managed at private for profit (PFP) and private not for profit (PNFP) directly observed treatment short course (DOTS) facilities.Methods:A retrospective review of treatment cards of TB patients managed between January 1, 2012, and June 30, 2012, in seven PFP and four PNFP DOTS facilities that served as treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Structures facilitating TB/HIV collaboration exist at all levels [3, 32], but integration is weak [28, 30]. Public-private partnership improved TB case detection and case holding [31, 3336]. Existence of evidence-informed guidelines and a steering committee [28]; capacity building, stakeholders meeting and quarterly supervision [32] enabled engagement of the private sector in TB control.…”
Section: Resultsmentioning
confidence: 99%
“…Structures facilitating TB/HIV collaboration exist at all levels [3, 32], but integration is weak [28, 30]. Public-private partnership improved TB case detection and case holding [31, 3336]. Existence of evidence-informed guidelines and a steering committee [28]; capacity building, stakeholders meeting and quarterly supervision [32] enabled engagement of the private sector in TB control.…”
Section: Resultsmentioning
confidence: 99%
“…In Myanmar, patients treated by private practitioners were more likely to be LTFU [86]. An interesting situation was observed in Nigeria where patients treated at private, not-for-profit (PNFP) DOT facilities were more likely to be LTFU [87]. The researchers concluded that "Patients managed at PFP [private, for-profit] DOT facilities were probably richer, had better education, nutrition, and knowledge of TB than patients managed at PNFP DOT facilities…" Indeed, the factors causing LTFU are not simple, and they are correlated with each other.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Despite the relatively high reported overall national TSR over the years, DRTB case notification in Nigeria has increased from 21 in 2010 to 1,686 in 2016 and a further increase of 35% from 1,686 in 2016 to 2,286 in 2017 [ 2 ]. In addition, a WHO survey in Mexico showed that one-third of patients who died from TB were managed by private practitioners [ 20 ]. TSR data disaggregated by type of facility (public versus private) is lacking in Nigeria, making efforts to monitor the success of recent DOTS program expanded into private facilities difficult.…”
Section: Introductionmentioning
confidence: 99%